Implementation of E-Government Jogja Smart Service in Building Jogja Smart City - Muna, Nilna; Salsabila, Nanda; Pradana, Vikko Hilmi (Jurnal Ilmu Administrasi Negara (JUAN), 2024)
This research discusses the implementation of the Jogja Smart Service (JSS) application as part of the E-Government concept to realize Yogyakarta as a smart city. The background of this study lies in the need for efficient and integrated public services in the digital era. The primary objective of this research is to evaluate the effectiveness of the JSS application in improving the quality of public services in Yogyakarta, focusing on its implementation, challenges, and impacts. The study employs a descriptive qualitative approach, utilizing data collection techniques such as literature review, application observation, and secondary data analysis. The findings indicate that JSS provides various services, including population administration, health, education, and tourism, which are easily accessible through a digital platform. Since its launch in 2018, the application has recorded over 82,949 users, with 49,816 from Yogyakarta and 33,132 from outside the region. However, the research also identifies several challenges, such as limited public awareness of the application, digital divides, and a less appealing user interface design. In conclusion, although the JSS application has made significant contributions to supporting smart city development, further efforts are needed to improve public awareness, digital infrastructure, and feature innovation to ensure optimal usage by all citizens. With these steps, JSS holds great potential to support Yogyakarta in becoming a smart and livable city